The Basis of John Chrysostom’s Teaching on Widowhood - Konieczko, Michał; Uciecha, Andrzej (Vox Patrum, 2022)
The paper presents the origins of John Chrysostom’s teaching on widowhood. The author analyses the most important factors that contributed to the shaping of John’s teaching aimed at widows. The first factor was his personal experience, such as the relationship with his mother or with befriended widows. The second factor was being under a strong influence of St. Paul’s teachings, especially the Letter to the Ephesians and the First Letter to the Corinthians. The last factor was a consequence of John’s distinction between the existential and essential sources of widowhood. The existential sources, i.e. mainly the imitation of virginity, are the result of John’s understanding of anthropology, while the essential sources are rooted in the unity of divine hypostases and arise from his view on Christian marriage. Chrysostom’s concept of widowhood takes on a concrete and vertical structure in which one can see a trace of the influence of philosophy and education which he received.